The prevalence and correlates of depression among older adults in greater Kumasi of the Ashanti region - Emmanuel K. Nakua; John Amissah; Phyllis Tawiah; Bernard Barnie; Peter Donkor; Charles Mock (BMC, 2023)
Abstract Background Approximately two million Ghanaians suffer from mental disorders including depression. The WHO defines it as an illness characterized by constant sadness and loss of interest in activities that a person usually enjoys doing and this condition is the leading cause of mental disorders; however, the burden of depression on the aged population is fairly unknown. A better appreciation of depression and its predictors is necessary to design appropriate policy interventions. Therefore, this study aims to assess the prevalence and correlates of depression among older people in the Greater Kumasi of the Ashanti region. Methods A cross-sectional study design with a multi-stage sampling approach was employed to recruit and collect data from 418 older adults aged 60 years and above at the household level in four enumeration areas (EAs) within the Asokore Mampong Municipality. Households within each EAs were mapped and listed by trained resident enumerators to create a sampling frame. Data was collected electronically with Open Data Kit application over 30 days through face-to-face interaction using the Geriatric Depression Scale (GDS). The results were summarized using descriptive and inferential statistics. A multivariable logistics regression using a forward and backward stepwise approach was employed to identify the predictors of depression in the study sample. All analyses were performed using STATA software version 16, and the significance level was maintained at a p-value < 0.05 and presented at a 95% confidence interval. Results The study achieved a response rate of 97.7% from the estimated sample size of 428 respondents. The mean age was 69.9 (SD = 8.8), and the distribution was similar for both sexes (p = 0.25). The prevalence of depression in this study was 42.1% and dominated by females, older adults (> 80 years), and lower economic class respondents. The rate was 43.4% for both consumers of alcohol and smokers with a history of stroke (41.2%) and taking medication for chronic conditions (44.2%). The predictors of depression in our study were being single, low class [aOR = 1.97; 95% CI = 1.18-3.27] and having other chronic conditions [aOR = 1.86; 95% CI = 1.59-4.62], and the inability to manage ones' own affairs [aOR = 0.56; 95% CI = 0.32-0.97]. Conclusion The study provides data that can inform policy decisions on the care of the elderly with depression in Ghana and other similar countries, confirming the need to provide support efforts towards high-risk groups such as single people, people with chronic health conditions, and lower-income people. Additionally, the evidence provided in this study could serve as baseline data for larger and longitudinal studies.